Effect of Mixing Constituent toward Engineering Properties of POFA Cement-Based Aerated Concrete - Khairunisa, Muthusamy; Mohd Warid, Hussin; Fadhadli, Zakaria (ASCE, 2010)
Palm oil fuel ash (POFA) cement-based aerated concrete is a new type of lightweight concrete produced by integrating POFA, a by product of palm oil mill as a partial cement replacement in aerated concrete. This paper presents the effects of using a different character of mixing constituent such as size of sand, various amounts of gas foaming agent, and a range of superplasticizer content on the compressive strength and density of aerated concrete with and without POFA. POFA passing 300-μm sieve was ground until its fineness is 99% passing 45-μm sieve was incorporated as partial cement replacement. POFA cement-based aerated concrete was prepared by adding 20% of POFA by weight of cementitious materials. It was discovered that POFA cement-based aerated concrete continues to exhibit higher strength compared to ordinary portland cement aerated concrete throughout the experimental program. Thus, this newly found material could be used as environmental friendly construction material since it possess adequate strength fulfilling the requirement in ASTM allowing it to be used as nonload-bearing element yet having lower density below 1,000 kg/m3 .